Development Wordwall Media to Teach Reading Skill in Recount Text Material at MA Ma’arif Udanawu: English - Nabila Rahma sari; Siti Rofi’ah; Istina atul Makrifah (Prodi Tadris Bahasa Inggris, 2023)
This research and development aims to represent the process and results of wordwall media development for teaching reading skills on recount text material. The research subject was class X IPA 5 MA Ma'arif Udanawu. The development procedure refers to the model ADDIE. Analysis, design, development, implementation, and evaluation are the five steps of the ADDIE paradigm. Observation and interview techniques were used as information gathering in the preliminary study. Meanwhile, to determine the feasibility of wordwall products, researchers used a questionnaire instrument that was given to content and media experts. Then a student response questionnaire was conducted to determine the level of student satisfaction with the media. A score of 96% was obtained in the very good category, per the evaluation of the material specialists. A rating of from media professionals is 92% was obtained which was classified in the Very Good category. In addition, the results of the student response questionnaire also scored 84% in the good category. Based on the overall assessment, the development of wordwall learning media in recount text material providing information for class X IPA 5 students can be declared feasible and suitable for use in teaching and learning activities.